2022
DOI: 10.1002/cncr.34196
|View full text |Cite
|
Sign up to set email alerts
|

Frail young adult cancer survivors experience poor health‐related quality of life

Abstract: BACKGROUND:Young adult cancer survivors experience frailty and decreased muscle mass at rates equivalent to much older noncancer populations, which indicate accelerated aging. Although frailty and low muscle mass can be identified in survivors, their implications for health-related quality of life are not well understood. METHODS: Through a cross-sectional analysis of young adult cancer survivors, frailty was assessed with the Fried frailty phenotype and skeletal muscle mass in relation to functional and quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…[27][28][29] Interestingly, premature aging has also been found in pediatric cancer patients, suggesting that frailty in younger patients follows a similar mechanism to that in the geriatric population. 26,30,31 Though there are many studies on the mechanism of frailty among adult cancer patients, to the best of our knowledge there are no studies among pediatric cancer patients. Such studies should be done in the future to Odds ratios (ORs) were calculated using logistic regression after adjusting for age, sex, race, insurance, income, hospital size, location and teaching status, cancer type, and node positive/metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] Interestingly, premature aging has also been found in pediatric cancer patients, suggesting that frailty in younger patients follows a similar mechanism to that in the geriatric population. 26,30,31 Though there are many studies on the mechanism of frailty among adult cancer patients, to the best of our knowledge there are no studies among pediatric cancer patients. Such studies should be done in the future to Odds ratios (ORs) were calculated using logistic regression after adjusting for age, sex, race, insurance, income, hospital size, location and teaching status, cancer type, and node positive/metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Another theory postulates that the mitochondrial bioenergetic function, which normally decreases with age, is further impaired in frail patients, which results in decreased muscle strength and endurance capacity 27–29 . Interestingly, premature aging has also been found in pediatric cancer patients, suggesting that frailty in younger patients follows a similar mechanism to that in the geriatric population 26,30,31 . Though there are many studies on the mechanism of frailty among adult cancer patients, to the best of our knowledge there are no studies among pediatric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is one of the most common cancer treatment methods; however, it may cause morbidity and delayed effects of acute radiation exposure (DEARE) in a variety of organ systems, including the cardiovascular, gastrointestinal, pulmonary, neurological, and hematopoietic systems, which collectively contributes to accelerated aging (Cupit‐Link et al, 2017; Tung et al, 2021). Clinical studies have shown that an increasing number of cancer survivors with DEARE, including childhood and adult patients, become frail after diagnosis and treatment, thus leading to the development of chronic diseases and geriatric syndromes prematurely (Miller et al, 2022; Pranikoff et al, 2022). These changes are referred to as accelerated or premature aging in long‐term survivors of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…and treatment, thus leading to the development of chronic diseases and geriatric syndromes prematurely (Miller et al, 2022;Pranikoff et al, 2022). These changes are referred to as accelerated or premature aging in long-term survivors of cancer.…”
mentioning
confidence: 99%
“…Advancements in cancer and supportive therapies have led to a growing population of young adult survivors 1,2 with more than 700,000 survivors now living in the United States 3 . The majority of young adult survivors experience significant impairments in health, quality of life, and lifespan with increased secondary cancers, cardiovascular disease, and endocrinopathies 4‐15 . The premature onset of aging‐related morbidities and functional impairment point to a process of accelerated aging in survivors, the underlying mechanism of which is not well understood 7,16,17 .…”
Section: Introductionmentioning
confidence: 99%